2005
DOI: 10.1126/science.1113247
|View full text |Cite
|
Sign up to set email alerts
|

Gas Adsorption Sites in a Large-Pore Metal-Organic Framework

Abstract: The primary adsorption sites for Ar and N2 within metal-organic framework-5, a cubic structure composed of Zn4O(CO2)6 units and phenylene links defining large pores 12 and 15 angstroms in diameter, have been identified by single-crystal x-ray diffraction. Refinement of data collected between 293 and 30 kelvin revealed a total of eight symmetry-independent adsorption sites. Five of these are sites on the zinc oxide unit and the organic link; the remaining three sites form a second layer in the pores. The struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
451
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 856 publications
(503 citation statements)
references
References 25 publications
42
451
0
5
Order By: Relevance
“…21 Using linear regression to calculate lattice parameter values at 30 K and 293 K, we find an increase in unit cell volume of 1.0 %, in exact agreement with XRD results that show the same percentage increase in unit cell volume (≈ 200 Å 3 or 0.1 Å in lattice parameter) over the same temperature range. 48 Dubbeldam et al 21 also reported similar agreement with experiment using their flexible force field. They also derived thermal-expansion coefficients from their simulations, concluding that IRMOFs outperform other contracting materials.…”
Section: Structural Validation and Mechanical Propertiessupporting
confidence: 58%
“…21 Using linear regression to calculate lattice parameter values at 30 K and 293 K, we find an increase in unit cell volume of 1.0 %, in exact agreement with XRD results that show the same percentage increase in unit cell volume (≈ 200 Å 3 or 0.1 Å in lattice parameter) over the same temperature range. 48 Dubbeldam et al 21 also reported similar agreement with experiment using their flexible force field. They also derived thermal-expansion coefficients from their simulations, concluding that IRMOFs outperform other contracting materials.…”
Section: Structural Validation and Mechanical Propertiessupporting
confidence: 58%
“…Powder X-ray diffraction (PXRD) showed that 1 can retain framework integrity even after being heated at 673 K for 2 h (Supplementary Fig. S4), which is much higher than those for other organic and organic-inorganic hybrid solids showing large thermal expansion properties [4][5][6][7][8][9][10][11][12][13][14][15]21,22 . Gas sorption measurements showed that 1 cannot adsorb N 2 or O 2 at 77 K up to P/P 0 E1 but adsorb considerable CO 2 at 195 K, with an apparent Langmuir surface area of 188 m 2 g À 1 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, a few flexible PCPs showed much larger thermal expansion than common solids because the open coordination frameworks are relatively flexible [4][5][6][7][8][9][10][11][12][13][14][15] . Whereas small positive thermal expansion (PTE, 0oao20 Â 10 À 6 K À 1 , a and b V for axial and volumetric thermal expansion coefficients, respectively) is an intrinsic property of common solids 16 , negative (NTE, ao0 K À 1 ) [17][18][19][20] , very large (|a|4100 Â 10 À 6 K À 1 ), tunable and other special thermal expansion behaviours are extremely rare and have received considerable theoretical and practical interest [21][22][23][24] , which may be rationally realized by PCPs.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The major applications currently being considered for these compounds involve gas storage, [9][10][11][12] catalysis, [13][14][15][16][17][18] separations, [19][20][21][22][23][24] as carriers for nano-materials 25,26 and drug delivery, 27,28 etc. For these applications, their high surface areas and unique pore structures are likely to offer many potential advantages over existing compounds.…”
Section: Introductionmentioning
confidence: 99%